Enhancing Arabic literacy through data-driven assessment: The impact of running records on reading evaluation and instruction - Almazroui, Karima (International Journal of Innovative Research and Scientific Studies, 2025)
Reading is a multifaceted cognitive process involving fluency, comprehension, and higher-order thinking. Traditional Arabic literacy assessments often focus on rote memorization and pronunciation accuracy, neglecting deeper cognitive and metacognitive reading processes. This study investigates the impact of running records, a formative assessment tool that captures real-time reading behaviors, on Arabic literacy instruction. Conducted in 17 public schools in Abu Dhabi, the mixed-methods study involved 120 students in Grades 2 to 5 and 20 Arabic language teachers trained in running record implementation. Quantitative data included measures of reading fluency, decoding accuracy, and comprehension. Qualitative data were collected through teacher interviews and classroom observations. Descriptive and inferential statistics assessed student progress, while thematic analysis captured teacher perspectives. Students assessed using running records showed a 23% reduction in reading hesitations, a 15% improvement in decoding accuracy, and a 31% gain in comprehension. Teachers reported that running records enhanced their ability to diagnose reading difficulties and tailor instruction. However, challenges such as time constraints and limited training affected implementation. The findings suggest that running records provide a more dynamic and insightful alternative to traditional Arabic literacy assessments. With targeted training and policy support, they can significantly improve literacy outcomes in Arabic-speaking classrooms.